Answer:
a) 7/4 b) 5 c) 2
Step-by-step explanation:
Logrithmic Rule for a and b
Let a, M, N be positive real numbers.
a)
logaM - logaN = loga(M/N)
log9(7) - log9(4) = log9 (7/4)
b)
logaM + logaN = logaMN
log2 (x) + log2(9) = log2(45)
x9=45
(x9)/9 = 45/9
x = 5
c)
Change of base formula.
logb(x)=logd(b)/logd(x)
x log6(5) = log6(25) divide each term by log6(5)
x log6(5) / log6(5) = log6(25) / log6(5) Cancel common factor log6(5)
x = log6(25) / log6(5)
x = log6(5^2) / log6(5)
Expand log6(5^2) by moving 2 outside the logarithm.
x = 2log6(5) / log6(5) cancel the like term log6(5)
x = 2
The first step to finding the developed form is to multiply each term in the parenthesis by 2
2 × 3x - 2 × 10
now,, youll need to calculate the product of the first multiplication set
6x - 2 × 10
finally,, multiply the last set of numbers
6x - 20
this means that the correct answer to your question is 6x - 20.
let me know if you have any further questions
:)
Let's use the slope formula!
m = y2 - y1 / (x2 - x1)
m = 6 + 7 / (-3 + 7) = 13/4
Answer:
c = 50
Step-by-step explanation:
We can set up an equation using the vertical angles theorem.
97 = 2c-3
100 = 2c
c = 50